Porosity, residual monomer and water sorption of conventional heat-cured, microwave-cured and cross-linked acrylic resins - Oliveira, Rodrigo Elias de; Nogueira, Fernando Neves; Mattos, Beatriz Silva Câmara (Clinical and Laboratorial Research in Dentistry, 2014)
This study compared the residual monomer release, water sorption and superfi cial porosity of different resins commonly employed in eye prostheses: heat-cured (HC); microwave-cured (MC) and self-curing cross-linked acrylic resins (SC). Four groups were established: G1, HC / water bath cycle; G2, MC / microwave cycle; G3, HC / microwave cycle; G4, SC. The amount of residual monomer was similar in G1 and G3, lower in G2 and higher in G4. Water sorption was similar in all groups. G2 showed more superfi cial porosity, and G1 and G3 were similar in this regard. Neither the conventional heat-curing cycle nor the microwave cycle affected the amount of residual monomer or porosity of the conventional heat-cured acrylic resin. Water sorption was not affected by the type of resin or polymerization cycle used. Residual monomer release and porosity were related to the type of resin employed rather than the polymerization cycle they were submitted to.